Taking an Extended Embodied Perspective of Touch: Connection-Disconnection in iVR - Price, Sara; Jewitt, Carey; Chubinidze, Dimitri; Barker, Ned; Yiannoutsou, Nikoleta (Frontiers in Virtual Reality, 2021)
Bringing touch into VR experiences through haptics is considered increasingly important for user engagement and fostering feelings of presence and immersion, yet few qualitative studies have explored users’ iVR touch experiences. This paper takes an embodied approach - bringing attention to the tactile-kinaesthetic body - to explore users’ wholistic experiences of touch in iVR, moving beyond the cutaneous and tactile elements of ‘feeling’ to elaborate upon themes of movement and kinetics. Our findings show how both touch connections and disconnections emerged though material forms of tactility (the controller, body positioning, tactile expectations) and through ‘felt proximities’ and the tactile-kinaesthetic experience thus shaping the sense of presence. The analysis shows three key factors that influence connection and disconnection, and how connection is re-navigated or sought at moments of experienced disconnection: a sense of control or agency; identity; and bridging between the material and virtual. This extended notion of touch deepens our understanding of its role in feelings of presence by providing insight into a range of factors related to notions of touch – both physical and virtual - that come into play in creating a sense of connection or presence (e.g. histories, expectations), and highlights the potential for iVR interaction to attend to the body beyond the hands in terms of touch.